Pentingnya Pemahaman dan Penerapan Moderasi Beragama pada Siswa dalam Menumbuhkan Sikap Toleransi di SMAN 4 Tana Toraja di Era Digitalisasi - Desiana Sikombong; Mersi Mersi; Elma Elma; Egayanti Assi; Norpa Kondo Tasik (Sinar Kasih: Jurnal Pendidikan Agama dan Filsafat, 2025)
This research is library research or research using library methods. The data collection technique used is to use sources originating from books and journals that are related to religious moderation. The type of research used is qualitative research, namely describing how religious moderation is in Indonesia. This paper will discuss the concept of intolerance that is developing in the lives of high school students, especially at SMAN 4 Tana Toraja. This research aims to provide understanding to behave tolerantly and avoid intolerant attitudes and it is important to provide understanding related to religious moderation to the nation's next generation in the era of digitalization.